First European quality of life survey income inequalities and deprivation - Fahey, Tony. (Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2005)
The recent enlargement of the European Union has changed the context within which poverty and social exclusion in the Member States is understood and has highlighted the need for an expanded approach to these problems. Enlargement has widened the gap in living standards between the richest and poorest Member States: median household income in the richest EU states such as Denmark and Germany is three to four times greater than in the poorest Member States, such as Latvia (Eurostat, 2004).